MyPage Pharmacia, India - Doutta, Gouttam, (SAGE Knowledge. Cases., 2017)
Pharmacia India was a new player in Indias pharmaceuticals industry. During the 2-3 years that had elapsed since its arrival, the company had sensed that something was seriously wrong deep inside its business process. The sales target was not being achieved and this was adversely affecting the credibility of the company and motivation level of the salespersons. They needed to take a fresh look at how Pharmacia was doing its business.